2008
DOI: 10.4028/www.scientific.net/msf.584-586.852
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic Transformations and Functional Stability in Ultra-Fine Grained NiTi Shape Memory Alloys

Abstract: Martensitic transformations in NiTi shape memory alloys (SMAs) strongly depend on the microstructure. In the present work, we investigate how martensitic transformations are affected by various types of ultra-fine grained (UFG) microstructures resulting from various processing routes. NiTi SMAs with UFG microstructures were obtained by equal channel angular pressing, high pressure torsion, wire drawing and subsequent annealing treatments. The resulting material states were characterized by transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…After HPT, specimens were annealed at 400 8C for 1 h to crystallize them from the amorphous state, producing an NC sample. [11] Samples of the CG, UFG, and NC materials were aged at 400 8C in air for 1, 10, and 100 h and quenched in water for the study of microstructural evolution. A temperature of 400 8C was selected for the long-term annealing based on previous investigations by Prokofiev et al [14] and Prokoshkin et al [15,30] which revealed that the NC grain size formed from the amorphous state can be maintained below 100 nm during annealing up to 400 8C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After HPT, specimens were annealed at 400 8C for 1 h to crystallize them from the amorphous state, producing an NC sample. [11] Samples of the CG, UFG, and NC materials were aged at 400 8C in air for 1, 10, and 100 h and quenched in water for the study of microstructural evolution. A temperature of 400 8C was selected for the long-term annealing based on previous investigations by Prokofiev et al [14] and Prokoshkin et al [15,30] which revealed that the NC grain size formed from the amorphous state can be maintained below 100 nm during annealing up to 400 8C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been great interest in the application of severe plastic deformation (SPD) to NiTi materials because the extremely fine grain sizes obtainable by SPD processing have been observed to enhance some mechanical and functional properties as compared to coarse grained (CG) materials. [8][9][10][11][12][13][14][15][16][17] Thus, arterial stent manufacturing presents an exciting and innovative potential application for SPD processing techniques, and the field of shape memory technology is developing strong ties with the research fields of ultra fine grained (UFG) and nanocrystalline (NC) materials. [11] The austenitic high temperature phase of NiTi (which has a B2 strukturbericht designation) can solve small amounts of excess Ni, and solubility decreases with decreasing temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Internal interfaces have a strong effect on the martensitic transformation, e.g. [9,11], and on the functional stability. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further details on the wire drawing procedure are given elsewhere [9]. In order to investigate the influence of dislocations on the functional stability, a mild cold work (10% deformation) was applied using a rolling mill of type Buehler EW 200 x 120 A.…”
Section: Alloy Production and Sample Preparationmentioning
confidence: 99%